STUDY OF FORMULATION OF HOVEN’S CARP (Leptobarbushaovenii)) FISH CAKE WITH ADDITION SAGO FLOUR IN DIFFERENT AMOUNTS TOWARD CONSUMER ACCEPTANCE - Elma Novianti; Suparmi Suparmi; Desmelati Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT The purpose of this research was to determine the level of consumer acceptance towards Hoeven’s carp (Leptobarbus hoevenii) fishcake with addition of sago flour in different amounts and obtained the nutritional content ofHoeven’s carp fishcake. The methodused was a non-factorial Completely Randomized Design (CRD) with addition of sago flour in different amountsfor fish cake processing which consisting of 4 levels: P0 (100 grams of tapioca flour), P1 (400 grams of sago flour), P2 (450 grams of sago flour), and P3 (500 grams of sago flour) with triplicates and 12 units of experimental units. The research parameters were organoleptic test (appearance, aroma, taste, and texture) and proximate analysis (moisture, protein, fat, and ash content). The result showed that P1treatment was most favorable by consumer acceptance, with characteristics of appearance was rather greyish colour, the specific aroma of hoven’s carp and sago flour seasoning, the specific taste of seasoning and Hoven’s carp meat), the chewy and compact texture. Meanwhile for proximate analysis that P1 treatment contained moisture, protein, fat, and ash was 53.22%, 7.87%, 4.25%, and 4.81%, respectively. Keywords: formulation, Hoven’s Carp Fish cake, Sago Flour